След от крыла бабочки: [роман] / Яна Лапутина - Лапутина Яна Евгеньевна (АСТ, 2011)
Экземпляры: СБ (201505) / Инвентарный номер: 50835 / Цена: 141.00 / Сис.шифр: Р2 / Авт.знак: Л 24 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6